Chapters on Chaucer - Malone, Kemp (Johns Hopkins University Press, 2019)
Originally published in 1951. Kemp Malone provides a guide to reading Chaucer's work that is intended for readers who are familiar with Chaucer's work but who are not Chaucerians. The first chapter places Chaucer in the historical and literary context of the fourteenth century. The other essays focus on Chaucer's poetry by providing historicized interpretations of Chaucer's work and methods for each poem.